2023
DOI: 10.1093/ecco-jcc/jjac190.0139
|View full text |Cite
|
Sign up to set email alerts
|

P009 IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells

Abstract: Background The pathogenesis of inflammatory bowel diseases (IBD) such as Crohn’s disease (CD) and ulcerative colitis (UC) is still incompletely understood. However, despite having been described back in the 1980s and reported to be involved in chronic inflammatory arthritis, the role of interleukin 3 (IL-3) signaling via the IL-3 receptor (IL-3R) in the development and perpetuation of chronic intestinal inflammation remains largely unexplored. In this study, we therefore aimed to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Having shown that, we sought to identify the mechanism for increased Ccl19-directed motility and increased recirculation of Il3r-deficient compared with Il3r-proficient T cells. To this end, we profiled unchallenged Il3r −/− and Il3r +/+ T cell from the thymus by bulk RNA sequencing, 23 which revealed 624 differentially expressed genes. Pathway enrichment analysis with the Database for Annotation, Visualization and Integrated Discovery (DAVID) demonstrated a substantial number of differentially expressed genes linked to the cytoskeleton (figure 4A,B), whereas the genes of key surface molecules involved in T cell trafficking including Ccr7 were similarly expressed (online supplemental figure 6).…”
Section: Il3r Deficiency Instructs Altered Cytoskeleton Architecture ...mentioning
confidence: 99%
“…Having shown that, we sought to identify the mechanism for increased Ccl19-directed motility and increased recirculation of Il3r-deficient compared with Il3r-proficient T cells. To this end, we profiled unchallenged Il3r −/− and Il3r +/+ T cell from the thymus by bulk RNA sequencing, 23 which revealed 624 differentially expressed genes. Pathway enrichment analysis with the Database for Annotation, Visualization and Integrated Discovery (DAVID) demonstrated a substantial number of differentially expressed genes linked to the cytoskeleton (figure 4A,B), whereas the genes of key surface molecules involved in T cell trafficking including Ccr7 were similarly expressed (online supplemental figure 6).…”
Section: Il3r Deficiency Instructs Altered Cytoskeleton Architecture ...mentioning
confidence: 99%
“…Importantly, microbiota-derived butyrate is associated with the induction and differentiation of regulatory T cells (Tregs) 33) , and the induction of Tregs is a central mechanism of host-microbiota homeostasis 34) . Moreover, activation of Tregs contributes to the amelioration of colonic inflammation 35,36) . Therefore, the effect of LKM512 on colonic inflammation might be mediated by microbial butyrate-induced activation of Tregs.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…IL-3 plays a contributory role in fostering the pro-inflammatory response by boosting the activation and functionality of immune cells. IL-3 has been associated with immune disorders such as sepsis [1], colitis [2,3], lupus nephritis [4] and arthritis [5]. In sepsis, IL-3 exacerbates acute inflammation by fueling a cytokine storm, and elevated IL-3 levels serve as a predictive indicator of mortality [1].…”
Section: Introductionmentioning
confidence: 99%